2019
DOI: 10.1155/2019/6927456
|View full text |Cite
|
Sign up to set email alerts
|

Association between Soluble Urokinase-Type Plasminogen Activator Receptor Levels and Chronic Kidney Disease: A Systematic Review and Meta-Analysis

Abstract: Background Chronic kidney disease (CKD) has become a global public health problem with a high prevalence and mortality. There is no sensitive and effective markers for chronic kidney disease. Previous studies proposed suPAR as an early predict biomarker for chronic kidney disease, but the results are controversial. Therefore, the purpose of the current meta-analysis is to evaluate the association between suPAR and CKD. Methods We searched the PubMed, Embase, Cochrane Library databases, and Web of Science befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In the kidney, suPAR can induce podocyte dysfunction and impair glomerular filtration function thus leading to the development of CKD ( Hayek et al, 2015 ; Lv et al, 2020 ), a phenomenon mostly found in focal segmental glomerulosclerosis studies ( Wei et al, 2011 ). 2019 a meta-analysis of the relationship between suPAR and kidney disease pointed out that suPAR was negatively correlated with eGFR, and in patients with CKD, especially ESRD patients suPAR levels were significantly higher than normal ( Shuai et al, 2019 ). Several subsequent studies suggested that close monitoring of suPAR could help in the early diagnosis and treatment of CKD and that suPAR levels were associated with CKD prognosis ( Rotbain Curovic et al, 2019 ; Shuai et al, 2019 ).…”
Section: Abnormalities Of Biomarkers In Dialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the kidney, suPAR can induce podocyte dysfunction and impair glomerular filtration function thus leading to the development of CKD ( Hayek et al, 2015 ; Lv et al, 2020 ), a phenomenon mostly found in focal segmental glomerulosclerosis studies ( Wei et al, 2011 ). 2019 a meta-analysis of the relationship between suPAR and kidney disease pointed out that suPAR was negatively correlated with eGFR, and in patients with CKD, especially ESRD patients suPAR levels were significantly higher than normal ( Shuai et al, 2019 ). Several subsequent studies suggested that close monitoring of suPAR could help in the early diagnosis and treatment of CKD and that suPAR levels were associated with CKD prognosis ( Rotbain Curovic et al, 2019 ; Shuai et al, 2019 ).…”
Section: Abnormalities Of Biomarkers In Dialysis Patientsmentioning
confidence: 99%
“…2019 a meta-analysis of the relationship between suPAR and kidney disease pointed out that suPAR was negatively correlated with eGFR, and in patients with CKD, especially ESRD patients suPAR levels were significantly higher than normal ( Shuai et al, 2019 ). Several subsequent studies suggested that close monitoring of suPAR could help in the early diagnosis and treatment of CKD and that suPAR levels were associated with CKD prognosis ( Rotbain Curovic et al, 2019 ; Shuai et al, 2019 ). 2021 Jhee et al evaluated the relationship between disease progression and suPAR in 751 CKD patients and demonstrated that suPAR levels were also independently associated with CKD progression ( Jhee et al, 2021 ).…”
Section: Abnormalities Of Biomarkers In Dialysis Patientsmentioning
confidence: 99%
“…A meta-analysis of patients with chronic kidney disease showed that in this patient population, elevated suPAR levels are also predictive of increased risk of cardiovascular disease (p < 0.001; HR: 3.06; 95% CI: 2.21-4.22; I 2 = = 0.0%). This prediction makes it possible, similarly to the population of patients with diabetes, to intensify the treatment and isolate the population requiring in-depth cardiological diagnostics [47].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed that suPAR levels may serve as a prognostic biomarker in CKD patients. The higher suPAR level has been shown to increase the risk of mortality, cardiovascular accidents, and ESRD occurrence [119].…”
Section: Supar Levels and Ckdmentioning
confidence: 99%